Spatial Organization of Proteasome Aggregates in the Regulation of Proteasome Homeostasis - Karmon, Ofri; Ben Aroya, Shay (Frontiers in Molecular Biosciences, 2020)
Misfolded proteins and insoluble aggregates are continuously produced in the cell and can result in severe stress that threatens cellular fitness and viability if not managed effectively. Accordingly, organisms have evolved several protective protein quality control (PQC) machineries to address these threats. In eukaryotes, the ubiquitin–proteasome system (UPS) plays a vital role in the disposal of intracellular misfolded, damaged, or unneeded proteins. Although ubiquitin-mediated proteasomal degradation of many proteins plays a key role in the PQC system, cells must also dispose of the proteasomes themselves when their subunits are assembled improperly, or when they dysfunction under various conditions, e.g., as a result of genomic mutations, diverse stresses, or treatment with proteasome inhibitors. Here, we review recent studies that identified the regulatory pathways that mediate proteasomes sorting under various stress conditions, and the elimination of its dysfunctional subunits. Following inactivation of the 26S proteasome, UPS-mediated degradation of its own misassembled subunits is the favored disposal pathway. However, the cytosolic cell-compartment-specific aggregase, Hsp42 mediates an alternative pathway, the accumulation of these subunits in cytoprotective compartments, where they become extensively modified with ubiquitin, and are directed by ubiquitin receptors for autophagic clearance (proteaphagy). We also discuss the sorting mechanisms that the cell uses under nitrogen stress, and to distinguish between dysfunctional proteasome aggregates and proteasome storage granules (PSGs), reversible assemblies of membrane-free cytoplasmic condensates that form in yeast upon carbon starvation and help protect proteasomes from autophagic degradation. Regulated proteasome subunit homeostasis is thus controlled through cellular probing of the level of proteasome assembly, and the interplay between UPS-mediated degradation or sorting of misfolded proteins into distinct cellular compartments.